A systematic review of the association between mental health and tuberculosis disease risk. (20th October 2021) - Hayward, SE; Deal, A; Rustage, K; Nellums, LB; Sweetland, AC; Boccia, D; Hargreaves, S; Friedland, JS
Abstract: Background: Tuberculosis (TB) and mental illnesses are highly prevalent globally and often co-exist. Whilst poor mental health is known to modulate immune function, whether mental disorders causally increase TB incidence is unknown. This systematic review examines the association between mental health and TB disease risk to inform clinical and public health measures. Methods: We carried out a systematic review following PRISMA guidelines (PROSPERO CRD42019158071). We searched MEDLINE, PsycINFO and PsycEXTRA databases alongside reference list and citation searching. Inclusion criteria were original research studies published 01/01/1970-11/05/2020 reporting data on the relationship between mental health and risk of TB disease. CASP and AXIS checklists were used to critically appraise included studies. Results: We screened 1546 records published over 50 years, resulting in data synthesised from 607, 184 individuals. Settings include Asia, South America, and Africa, and both mood (e.g. depression) and psychotic (e.g. schizophrenia) disorders are investigated. Robust evidence from cohort studies in Asia shows that depression and schizophrenia can increase risk of TB disease, with effect estimates ranging from HR = 1.15 [95% CI 1.03-1.28] to HR = 2.63 [95% CI 1.74-3.96] for depression and HR = 1.52 [95% CI 1.29-1.79] to RR = 3.04 for schizophrenia, and a dose-response relationship reported in one study. These data are consistent with data from cross-sectional studies, such as a large survey across low- and middle-income countries (n = 242, 952) reporting OR = 3.36 [95% CI 3.01-4.50] for a depressive episode in those with TB versus those without. Conclusions: Individuals with mental illnesses including depression and schizophrenia experience increased TB incidence and represent a high-risk population to target for screening and treatment. Integrated care for mental health and TB is needed, and interventions tackling mental illnesses and underlying drivers may help reduce TB incidence globally. Key messages: This systematic review examines data from 607, 184 individuals and finds evidence that mental health is a risk factor for TB disease. Those suffering from depression and schizophrenia are an at-risk population that could be identified and targeted for TB screening and treatment.